Vanadio en agua de bebida animal de tambos del sudeste de Córdoba, Argentina - Pérez Carrera, A. (2014)
In this paper, vanadium levels, in animal drinking water, were quantified in water samples from 25 dairy farms located in the department of Union, southeast of the province of Cordoba, Argentina. In addition, total dissolved solids (TDS) and major ions were considered in order to determine the quality of water source used for livestock. Analyzed data showed that 48% of farms use a groundwater from the freatic aquifer (3 to 15 m), for animal drinking water, whose quality is worst than water from deeper wells (80 to 120 m). It was also noted that all the samples from the freatic aquifer exceeded the maximum vanadium levels considered for animal drinking water, reaching more than 6 mg/L. Regarding the water from deeper wells, less than 10% of them have vanadium concentrations above the recommended level, presenting a maximum level of 0.3 mg/L. The present study suggests that the water from the freatic aquifer would not be safe for use as water for livestock drinking; because of the levels of vanadium, arsenic, fluoride, chloride and sulphate.